Articulation functions for the common word lists between Kannada and Telugu languages for native speakers of Kannada - CA, Usha (Journal of All India Institute of Speech and Hearing)
The present study is aimed at obtaining the articulation functions for the word lists CQmmon to Kannada and Telugu languages for the native speakers of Kannada. In addition, effect of language of the carrier phrase on discrimination scores was also investigated. The lists - of words were recorded with two carrier’ phrases (one eaCh, of Kannada and Telugu languages) on magnetic -tapes.